NotisMe!: Crowdsourced Student Tasks Reminder with Gamification - Mohd Hizal, Muhammad Haziq; Ahmadon, Fadzlin; Mohd Rozi, Nor Aizie Izzaty; Maarof, Haziq Iqbal; Mohd Shahrin, Nadia Batrisyia (2020)
Students, tasks and time is inextricably linked. Each student is required to complete their tasks or assignments within a given period of time. However, for a certain number of students, they do not notice that there is a task that has been assigned to them and they lack motivation to finish the task given by lecturers. Therefore, the aim of the developed application is to increase students’ awareness of the task that has been assigned to them and increase the students’ motivation in finishing the task given to them. Mobile Application Life Cycle (MADLC) model has been chosen as the methodology for this project because it is frequently used in developing a mobile application. Gamification which consists of several game elements such as challenges, rewards, points, and badges are implemented in the application. The platform chosen for the application is android mobile-based platform. This project is about a mobile application that reminds students about tasks using the techniques of crowdsourcing and gamification. This application is a reminder application that allows users to share assigned tasks with their groups and reward users in term of badges for adding the tasks and completing them. Functionality testing has been carried out for the developed application. The outcome of the test is successful as all the twenty-two test cases is passed. Further improvement can be added to the application, for instance, add features like chat and leader board to the application. In conclusion, the application has been successfully developed and all the objectives have been accomplished.